Family relationship quality during the COVID‐19 pandemic: The value of adolescent perceptions of change. (1st December 2021) - Martin‐Storey, Alexa; Dirks, Melanie; Holfeld, Brett; Dryburgh, Nicole S.J.; Craig, Wendy
Abstract: Introduction: Adolescents typically spend decreasing amounts of time with family members, but the COVID‐19 pandemic changed this pattern for many youth. The objective of the current study was to better understand adolescents' perceived change in family relationship quality, and how these perceptions were related to psychosocial functioning during the COVID‐19 pandemic, accounting for more traditional measures of family relationship quality. Understanding how adolescents perceived change in relationship quality with family members during the pandemic offers novel insight into adolescents' relationships with their families and psychosocial functioning during this period. Method: A sample of Canadian adolescents ( N  = 605, ages 14 to 18, 53% girls), was employed to examine patterns of adolescents' perceived change in relationship quality with parents and siblings since the start of the pandemic, accounting for relationship quality, pandemic‐related characteristics, and demographic variables. Results: Four latent profiles were identified: youth who perceived (1) low change, (2) improvement only, (3) moderate instability and (4) high instability in relationship quality. Higher perceived instability was associated with poorer functioning, with youth who reported only improvement reporting the highest overall level of functioning. Conclusions: Adolescent perceptions of change in relationship quality were heterogeneous, and contribute to psychosocial functioning over and above their general evaluations of relationship quality. In particular, youth who perceive considerable change in their relationships with siblings and parents may require additional support in response to the COVID‐19 pandemic.